ANALYSIS OF PENIS SIZE DIFFERENCES IN PATIENTS WITH SEVERE ERECTILE DYSFUNCTION NON-RESPONSIVE PDE5i WITH MESENCHYMAL STEM CELL SECRETOME FROM UMBILICAL CORD - Wibowo, Kristophorus Jonathan; I’tishom, Reny; Soebadi, Mohammad Ayodhia; Atmaja, Muhammad Hidayat Surya; Supardi, Supardi; Margiana, Ria; Amalia, Fatkhurrohmah Leo (Folia Medica Indonesiana, 2025)
The ineffectiveness of PDE5i[-10pc]AU: Please provide the affiliation of all authors. therapy is indicated by the patient’s unresponsiveness to oral medication, evidenced by insufficient erection after four attempts with the dosage recommended by the manufacturer. Consequently, the application of regenerative therapy may be seen as an effort to stimulate a response or improvement in erectile function, especially in individuals with erectile dysfunction who exhibit no significant progress after utilizing PDE5 inhibitors. Regenerative therapy seeks to repair damaged erectile tissue, with the objective of enhancing erectile function and rehabilitating tissue impacted by existing comorbidities. The secretome denotes the aggregate of chemical compounds and biological factors secreted by cells into the extracellular environment. These secretory factors are essential for various biological processes, including maintaining homeostasis, promoting tissue growth and repair, regulating immune responses, controlling inflammation, stimulating angiogenesis, inducing apoptosis, degrading proteins, facilitating cell adhesion, and organizing the extracellular matrix (ECM). We calculated the sample size using a normal significance level with α = 0.05 and a standard power corresponding to β= 0.20. Metode for this research used a pre–post test design and was conducted from April to May 2024 at the Andrology Clinic of Dr. Soetomo General Academic Hospital, Surabaya, involving a sample of 7 patients with severe ED who were non-responders to PDE5i and had type 2 diabetes mellitus. SPL, FPL, and penile circumference were evaluated before and one month after intracavernosal injection of UC-MSC secretome. This study revealed substantial variations in SPL, FPL, and penile circumference among erectile dysfunction patients who were non-responders to PDE5i, both prior to and following the infusion of mesenchymal stem cell-derived secretome from the umbilical cord. SPL rose by 0.715 cm (p-value: 0.047), FPL was increased by 0.643 cm (p-value: 0.022), and penile circumference was enlarged by 0.50 cm (p-value: 0.014). These enhancements were noted on day 30 post-data collection, It is concluded that intracavernosal secretome UC-MSC therapy for severe PDE5i-nonresponsive ED demonstrates improvement in penile blood flow; however, further studies with longer evaluation periods are still needed to obtain more robust results.